2019
DOI: 10.1111/ssqu.12614
|View full text |Cite
|
Sign up to set email alerts
|

Structural Inequality and Ethnic Bloc Voting*

Abstract: Objective. A large body of ethnic politics literature suggests that horizontal inequalities exacerbate ethnic conflict. However, the relationship between intergroup inequality and ethnic bloc voting behavior has escaped empirical analysis. We test the relationship between ethnic bloc voting and horizontal inequality by examining how relative disparity affects individuals' probability of supporting the same political party as other co-ethnics. Methods. This project uses data from the Integrated World and Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Next, as Huber and Suryanarayan (2016) argue, inequality contributes to the increasing salience of ethnicity by making it easier for groups to organize bargaining. Inequality reduces the costs of committing to specific policy outcomes designed to benefit specific groups, which increases the likelihood of ethnic based organizing, increasing the likelihood of supporting an ethnic party (Houle 2015; Stewart and McGauvran 2019). Economic inequality also reduces cross-pressure, a potential situation where voters are conflicted between options that represent their ethnicity and those that represent their class, reduce the incentive for ethnic voting (Dunning and Harrison 2010), on voters.…”
Section: Why Economic Inequality Increases Ideological Extremismmentioning
confidence: 99%
See 4 more Smart Citations
“…Next, as Huber and Suryanarayan (2016) argue, inequality contributes to the increasing salience of ethnicity by making it easier for groups to organize bargaining. Inequality reduces the costs of committing to specific policy outcomes designed to benefit specific groups, which increases the likelihood of ethnic based organizing, increasing the likelihood of supporting an ethnic party (Houle 2015; Stewart and McGauvran 2019). Economic inequality also reduces cross-pressure, a potential situation where voters are conflicted between options that represent their ethnicity and those that represent their class, reduce the incentive for ethnic voting (Dunning and Harrison 2010), on voters.…”
Section: Why Economic Inequality Increases Ideological Extremismmentioning
confidence: 99%
“…Ethnic parties adopt this strategy because, unlike mainstream parties, they are limited in their ability to increase vote share by making appeals across ethnic lines, which often includes moderating policy preferences or targets (Gormley-Heenan and Macginty 2008; Mitchel et al 2009; Zuber 2013). Recent research has concluded that increases in inequality are associated with increases in ethnic voting (Houle 2015; Stewart and McGauvran 2019), often driven by individuals turning to co-ethnic parties or candidates in an attempt to receive more focused benefits (Bratton et al, 2012). In fact, this research indicates that inequality is a much better predictor of ethnic political mobilization than either individual (Stewart and McGauvran 2019) or group-based resources (Cederman et al, 2011).…”
Section: Why Between Group Inequality Makes Ideological Extremism a Successful Tacticmentioning
confidence: 99%
See 3 more Smart Citations